The impact of public sector employment on regional economic activity: countering seasonal fluctuations and economic shocks. (2nd January 2023) - O'Brien, Martin
ABSTRACT: This research documents multidimensional facets of public value provided by public sector employment in regional Australia. Evidence and estimates of the contribution and impact of public sector employment to regional labour markets and economic activity are documented for the Illawarra, South Coast and Capital regions of New South Wales, Australia. Using a mixed methods approach, results presented illustrate that public sector employment embodies a significantly larger proportion of total employment and economic activity in most regional labour markets compared to Greater Sydney or Australia in general. Other analyses reveal both counter-seasonal and countercyclical contributions of public sector income and spending to regional economic activity. The main finding of this research is that public sector employment provides a stable foundation to regional economies that are otherwise strongly influenced by seasonal patterns associated with tourism and agriculture. The importance of public sector employment to the regional economies has been amplified in recent crisis periods associated with large scale bushfires and COVID-19.